Effects of Abscisic Acid on Bioactive Compounds and Postharvest Quality of Climacteric and Non-Climacteric Fruit - Nafi Ananda Utama; Prawidya Tyas Utami; Muhammad Galang Akbar Yulansyah Daryanto; Sukuriyati Susilo Dewi (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2023)
Abscisic acid (ABA) is a growth regulatory substance that plays an important role in various processes in the cell, such as plant adaptation to environmental threats, seed development, dormancy, budding, plant development, and fruit ripening. Another important role of abscisic acid is increased antioxidant capacity, total phenol content, total carotenoid, and anthocyanin content. The content of bioactive compounds such as antioxidants is a parameter of fruit quality that can decrease due to improper postharvest handling. Many postharvest treatments have been conducted to maintain or delay the declining of bioactive compounds in fruits. This current research was done to determine the various abscisic acid concentrations on papayas and cucumbers' bioactive content. The experiment was arranged in a completely randomized design with three replications. The data were expressed as mean ± standard deviation and analyzed using SAS (Statistical Analysis Software). Significant differences between means were determined by the Student's t-test, with p-values less than 0.05 considered significant. Results of the research regarding color testing, DPPH, total phenol content, and total soluble solids showed that abscisic acid with 380 µMol or 100 mg/l concentration could increase the total phenol content, antioxidant capacity, and total soluble solids in papayas (climacteric fruit) during the ripening. However, applying abscisic acid with 100 µMol on cucumbers (non-climacteric fruit) showed no significant effect on total phenol, antioxidant capacity, and soluble solids compared to the control group. The results showed that during the ripening of climacteric fruit, ABA enhanced the content of bioactive compounds and improved postharvest quality. This effect was not observed in non-climacteric fruit.